Computational insights into the inhibitory effects of PFAS 14 on colorectal cancer targeting GSTA1 through competitive binding - Jinxiao Li; Yanran Wu; Pian Ye; Dongmei Zuo; Shuangjiao Deng; Ran Pang; Huarong Li (Ecotoxicology and Environmental Safety)
This study employed computational biology approaches to investigate the interactions between per- and polyfluoroalkyl substances (PFAS) and key colorectal cancer (CRC) proteins. The results indicate that PFAS may influence CRC progression by modulating multiple proteins, particularly glutathione S-transferase A1 (GSTA1). Computational analysis revealed that PFAS 14 exhibits high binding affinity for GSTA1, occupying its glutathione-binding site. Further simulations confirmed the stable binding of PFAS 14 across different environments, forming persistent hydrogen bonds and water bridges, suggesting a potential inhibitory effect on GSTA1.GSTA1, a key member of the glutathione S-transferase family, plays a critical role in detoxification by catalyzing the conjugation of glutathione to electrophilic compounds. Dysregulation of GSTA1 has been implicated in cancer progression and chemoresistance. In CRC, altered GSTA1 expression may affect tumor metabolism and drug response, making it a potential therapeutic target.This study identifies GSTA1 as a key target of PFAS interactions, suggesting that environmental PFAS exposure may influence CRC by interfering with detoxification mechanisms. The competitive inhibition of GSTA1 by PFAS 14 may impact cancer cell survival and progression. Future research should integrate experimental validation to assess its phenotypic effects and evaluate PFAS 14 as a potential GSTA1 inhibitor.